1987
DOI: 10.3758/bf03334746
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent counting of two and three events in a serial anticipation paradigm

Abstract: Rats were runway trained with four different series of reward events for the purpose of determining if two different number cues (two and three) could be adequately employed to correctly anticipate a terminal nonreward in the series. In two of the series, two rewarded runs always occurred prior to terminal nonreward; one of these series always began with a nonrewarded run, NRRN, and the other did not, RRN. For two other series, three rewarded runs predicted terminal nonreward, NRRRN and RRRN. Each rat experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…For example, Burns and Sanders (1987) asked whether rats can be cued independently to enumerate a different number of reinforcements depending on the context of the series. They trained rats on an alternating series of RRN and NRRN under one level of illumination, and RRRN and NRRRN under a different level of illumination, and they found that in both conditions the subjects learned to run more slowly on the last trial.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Burns and Sanders (1987) asked whether rats can be cued independently to enumerate a different number of reinforcements depending on the context of the series. They trained rats on an alternating series of RRN and NRRN under one level of illumination, and RRRN and NRRRN under a different level of illumination, and they found that in both conditions the subjects learned to run more slowly on the last trial.…”
Section: Discussionmentioning
confidence: 99%
“…Possible sources of position cues have been reviewed elsewhere (e.g., Burns et aI.,2(04). Briefly, we might imagine position cues being based on an intE~rnal representation of the series positions (0 ' Amato, 1991), or the animals might somehow count the trials or rewards in a series and use number to tag the ordinal positions (Burns & Sanders, 1987;Capaldi & Miller, 1988). Another interesting possibility is that position-learning effects arise from the development of response patterns (Burns et aI., 2004).…”
Section: Discussionmentioning
confidence: 99%